Theories and Practices of Development: An Anthropological Perspective - Pokharel, Binod (Dhaulagiri Journal of Sociology and Anthropology, 2014)
Development is a contested ideology and concept. There is a long anthropological tradition that looks at development actions and events from different perspectives. Each perspective has its own explanation, methodology, epistemology, interest articulation, imagination and policy agenda. It seems that development policy and practice has been periodically regenerated and reformulated with new ideas and thinking. In recent years, anthropologists have increasingly been involved in the ethnographic study of development projects, such as strategies, policies, practices and organizations. Despite the growing number of development literatures in Nepal, few studies have examined interfaces between development projects and local politics. Broadly, there are two traditions of looking at the community development in Nepal. The first category of literature is basically concerned with social transformations through development intervention. The second type is more interpretive and focuses on discourse analysis. DOI: http://dx.doi.org/10.3126/dsaj.v7i0.10435 Dhaulagiri Journal of Sociology and Anthropology Vol. 7, 2013; 1-30